Research on the production of useful protein using silkworm (Bombyx mori) as a bioreactor - YANG Rui-li; JIN Yong-feng; WU Yu-cheng; ZHANG Yao-zhou; WU Xiang-pu (浙江大学学报. 农业与生命科学版, 2001)
Summarized the basic principle, production steps, achievements of expression foreign genes and pharmaceuticals development using Silkworm/BmNPV Expression System, and introduced technological development of the mass production of useful protein in silkworm, and revealed the bright prospect.